Effect of the COVID-19 pandemic and lockdown on cancer stage distribution and time to treatment initiation using cancer registry data of the Swiss cantons of Zurich and Zug from 2018 to 2021 - Flurina Suter; Miriam Wanner; Andreas Wicki; Dimitri Korol; Sabine Rohrmann (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Swiss healthcare institutions conducted only urgent procedures during the COVID-19 lockdown, potentially leading to a lack of care for other severe diseases, such as cancer. We examined the effects of the pandemic on cancer stage distribution and time between cancer diagnosis and treatment initiation using population-based cancer registry data. Methods The study was based on data of the cancer registry of the cantons of Zurich and Zug from 2018 to 2021. Cancer stage distribution was analysed descriptively and with a Pearson’s Chi-squared test. Time between cancer diagnosis and treatment initiation was determined in days and analysed descriptively and by fitting Quasipoisson regression models. Results For all-cancer and colorectal, lung, and prostate cancer statistically significant evidence for a difference in cancer stages distribution among the incidence years was observed. Based on the all-cancer regression models, longer time to treatment initiation (TTI) was observed for patients diagnosed in 2021 and receiving surgery (Rate Ratio = 1.08 [95% confidence interval 1.03, 1.14]) or hormone therapy (1.20 [1.03, 1.40]) compared to those diagnosed in 2018/19 receiving those therapies. We observed no difference in TTI between cancer patients diagnosed in 2020 compared to 2018/19 for any of the therapies investigated, except for chemotherapy with shorter TTI (0.92 [0.86, 0.98]). Conclusion The observed effects on cancer outcomes in 2020 and 2021 compared to 2018/19 coincided with the beginning of the COVID-19 pandemic in Switzerland in 2020 onwards. Short- and long-term effects of the pandemic on cancer outcomes and the public healthcare system were observed. However, we cannot exclude that the implementation of the new Swiss law on cancer registration in 2020 explains part of our observations.